English for hotel (Kun Fayakun, 2019)
Hotelprovides lodging ang sometimes provides meals and various personal service for the hotel guests. A good hotel provides many comforts and conveniences. The hotel's different departments ang their functions play a crucialrole in ensuring the successful run of the business, while providing a positive experience to its guests.